Estudio de comercialización de madera aserrada y otros productos maderables en los depósitos de Iquitos metropolitano, Iquitos, Peru, 2022 - Najar del Aguila, Fatima Paola (2023)
The present study has been developed in the city of Metropolitan Iquitos that covers the districts of Belen, San Juan, Punchana and Iquitos belonging to Loreto region, with the purpose of determining the current state of the commercialization of sawn timber and other timber products in the deposits of Metropolitan Iquitos. From the results obtained, it can be seen that there are six important supply centers for sawn timber and other timber products, and they are: Bellavista Nanay, Belen Navarro Cauper, Curva de Moronacocha, Santa Clara and Santo Tomas. There are 21 companies registered by GERFOR - GOREL that are dedicated to the commercialization of sawn timber and other timber products, of which 15 (71%) are in activity, 01 (5%) without activity, 03 (14%) with temporary suspension and 2 (10%) have been discharged. 57% (12) of the companies are located in San Juan, 10% (2) in Belen, 33% (7) in Iquitos and Iquitos and only 10 (2) are located in the district of Belen. The most used species for sawmilling and the most commercialized in the market are moena, yacushapana, quillavara, requia, andiroba, catahua, cumala, catahua, pashaco and capinuri and among other timber products we have caibros, beams, solera, tongue and groove wood mats. The income obtained in this type of business according to the size of the company is not greater than S/. 216,572.95 per year or a monthly income of S/. 18,047.74